IDENTIFIKASI KESALAHAN SISWA BERKECERDASAN VISUAL SPASIAL DALAM MENYELESAIKAN SOAL MATEMATIKA BANGUN RUANG SISI DATAR - Romadhoni, Linda; Setiawan, Toto' Bara; Hobri, Hobri (Kadikma, 2017)
Abstract. This research is descriptive research with qualitative approach. The purpose of this study was to identify errors made by students of spatial, moderate, and low visual intelligence in solving math problems. The instrument used is a sheet of spatial visual intelligence test test, a sheet of flat space side wake, and interview guide. The subjects used were 2 students with high spatial visual intelligence, 2 students with medium spatial visual intelligence, and 2 students with low spatial visual intelligence. This grouping is based on the results of a spatial visual intelligence test. The student error indicators used are 5 types, including fact errors, concept errors, operation errors, principle errors, and other errors. Factual errors, operations, and principles merupapakan characteristics of visual intelligence spatial problem solving, while the error of the concept consisting of the error of drawing objects including the characteristics of the imagination and determine the pattern is a pattern search characteristics. Students with high spatial visual intelligence make a mistake of facts and operational errors. Students with spatial visual intelligence are making a mistake of facts, concept errors, operational errors, and other errors. Students with low spatial visual intelligence make a mistake of facts, concept errors, operational errors, principle errors, and other errors. When viewed from the characteristics of spatial visual intelligence, students with high spatial visual intelligence make mistakes on the characteristics of problem solving, students with spatial visual intelligence are making mistakes on the characteristics of imagination, conceptualization, problem solving and pattern searching, as well as students with low spatial visual intelligence performing the same thing. Key Words: Spatial Visual Intelligence, Student Error Identification, Geometric the Flat Side